CDNA microarray analysis of cancer associated gene expression profiles in malignant peripheral nerve sheath tumours. Issue 2 (27th January 2006) - Karube, K; Nabeshima, K; Ishiguro, M; Harada, M; Iwasaki, H
Abstract : Background: Malignant peripheral nerve sheath tumour (MPNST) is a highly aggressive malignancy that arises within peripheral nerves, and is associated with poor prognosis. Little is known about the underlying biology of MPNST, especially the mechanisms involved in cell proliferation, invasion, or escape from apoptosis. Aims: To identify genes differentially expressed in MPNST compared with benign tumours, such as neurofibromas and schwannomas, by means of cDNA microarray analysis. Methods: Six MPNST cases and five benign cases (three schwannomas and two neurofibromas) were analysed. Results: Six genes (keratin 18, survivin, tenascin C, adenosine deaminase, collagen type VIa3, and collagen type VIIa1) were significantly upregulated in MPNST, whereas one gene, insulin-like growth factor binding protein 6, was downregulated in MPNST. Survivin and tenascin C expression was validated by reverse transcription polymerase chain reaction. Immunohistochemistry confirmed upregulation of survivin in MPNST at the protein level in six of eight cases compared with benign tumours. Tenascin C was also expressed at the invasive front and tumorous stroma in all MPNST cases. MPNST cells expressed tenascin C in four of nine cases. Conclusions: Survivin and tenascin C may be associated with the malignant potential of MPNST and could be considered as potential therapeutic targets.